Correlation of SARS-CoV2 Viral Growth on Cultures, Ct Values, SARS-CoV-2 Variant and Vaccination Status in Asymptomatic, Pre-Symptomatic and Post-Infection Asymptomatic COVID Patients. (9th November 2022) - Kaur, H; Morris, C P; Gallagher, N; Norton, J; Eldesouki, R; Mostafa, H; Sachithanandham, J; Pekosz, A
Abstract: Introduction/Objective: COVID-19 large scale immunizations have helped control the infectious spread, but breakthrough infections are still observed and some of these patients remain asymptomatic. In this study, we compared the viral growth characteristics with vaccination status in asymptomatic patients. Methods/Case Report: We searched our institutional laboratory database for asymptomatic patients infected with delta variant (November-December 2021, n=65) and omicron variant (December 2021, n=68), that were further classified as "truly asymptomatic", "pre-symptomatic" and "post-infection asymptomatic" based on detailed chart reviews. The patients' left-over nasopharyngeal swab samples' cycle threshold values and the recovery of infectious virus in cell culture were compared. Results (if a Case Study enter NA): In the delta cohort, out of 65 asymptomatic patients, 36 were truly asymptomatic, 26 presymptomatic and 3 post infection asymptomatic patients. In the omicron cohort, out of 68 asymptomatic patients, 45 were truly asymptomatic and 23 were presymptomatic patients. The vaccination rate was 59% in truly asymptomatic (delta cohort=56%, omicron cohort=62%), 55% in presymptomatic (delta cohort=50%, omicron cohort=61%) and 67% in post-infection patients (delta cohort only). There was no significant difference in the Ct values of truly asymptomatic (mean Ct=21.08), presymptomatic (mean Ct=20.30) and post-infection asymptomatic patients (mean Ct=20.84) in the combined cohort (p=0.78) and in the delta (p=0.95) or omicron (p=0.45) subcohorts. The Ct values were not correlated with the vaccination status of the patients (vaccinated patients mean Ct=20.56, non-vaccinated patients mean Ct=20.16, p=0.68). Samples with positive viral growth on cultures had significantly lower Ct values (mean Ct= 17.16), compared to samples with negative viral culture results (mean Ct= 24.61) (p<0.0001). The viral growth on culture was not associated with the symptom status, SARS-CoV-2 variant type (delta vs omicron) and vaccination status of the patients in the delta and omicron subcohorts. Conclusion: Our findings show that there is no significant correlation between vaccination status and viral loads and culture results in asymptomatic patients.